Translation Equivalence of Culture-Specific Items in Donna Widjajanto’s Rendition of The Field Guide - Setiawan, Kurnia Ari (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study investigates translation equivalence in the Indonesian version of The Spiderwick Chronicles (Book 1: The Field Guide) by Tony DiTerlizzi, focusing on 69 culture-specific items (CSIs). Applying Nida and Taber’s framework of formal and dynamic equivalence, the research aims to determine the predominant strategy used in rendering culturally bound expressions. Using a descriptive qualitative approach, the CSIs are categorized into five cultural domains: ecology, material culture, social culture, organizations and customs, and anthroponyms. The analysis reveals a strong preference for formal equivalence, with the highest occurrences in the categories of organizations (36.2%) and material culture (34.8%). Borrowing—both pure and naturalized—emerges as the dominant translation technique, particularly for items related to anthroponyms, religious concepts, and ecological terms. This reliance on source-language structures suggests a translator orientation that prioritizes fidelity over cultural adaptation. While this strategy preserves source-text integrity, the study recommends a more adaptive approach to improve clarity and cultural accessibility for target readers. Overall, the findings highlight the importance of balancing semantic accuracy and cultural resonance in the translation of culture-specific items.